Inštrumentálny realizmus ako možné východisko teoretickej reflexie vyučovania matematiky - Ladislav Kvasz (Karolinum Press, 2020)
The aim of the paper is to present an epistemological position called instrumental realism and to show how this position can be used as a tool for the analysis of different approaches to mathematics education. Instrumental realism is based on the conviction that any successful study of a particular segment of reality must on the one hand take into account the specific features of the particular segment of reality that we are studying. On the other hand, it must take into account the particular epistemic tools, by means of which we approach this segment of reality. In the case of physics, biology, or psychology, these two requirement do not seem controversial. Nevertheless, in the case of mathematics to speak about mathematical reality that we study or about the instruments that we use is much less obvious. Instrumental realism thus opens a new perspective on knowledge acquisition, that, as we believe, has many important consequences for mathematics education.